Breath-focused mind-body therapy for global mental health: war and other mass disasters - Patricia L. Gerbarg; Richard P. Brown (Academia Mental Health & Well-Being)
New models for mental healthcare are needed to address the global epidemic of depression, anxiety, and post-traumatic stress caused by wars and other mass disasters. Excess stress and trauma are major drivers of mental health disorders. Mind-body interventions that balance and strengthen stress response systems can prevent and improve these conditions. Evidence-based, trauma-informed, breath-focused mind-body treatments can relieve psychological, emotional, cognitive, and somatic symptoms in survivors and caregivers during and after disasters. This overview describes Breath-Body-Mind programs that exemplify a new model of care using online platforms to deliver stress and trauma relief as well as for training community extenders to teach greater numbers of disaster survivors and frontline workers in Ukraine, Rwanda, Türkiye, Ireland, and other countries. Understanding neurophysiological processes that contribute to the beneficial effects is important for selecting and optimizing the safest, most effective, and efficient methods for stress and trauma relief. Teaching professionals and lay providers how to create an engaging, safe, supportive environment online and in person enables a small group to deliver accessible, culturally syntonic, non-stigmatizing, sustainable mental health interventions to large populations impacted by disasters. This overview offers guidelines for a scalable mind-body intervention, plausible mechanisms of action, summaries of studies, and fieldwork in mass disasters since the 2017 Rohingya genocide in Myanmar (Burma), and future directions.